Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Mie Gacoan Cabang Marapalam - Ziqra Ahmad Fauzi; Siska Lusia Putri (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the Effect of Product Quality and Service Quality on Purchasing Decisions at Mie Gacoan, Marapalam branch in Padang City (Case study of undergraduate students of Management at Unidha)